Condensation mechanism of AgCl and NaCl island films on a nickel substrate - Gladkikh, N.T.; Dukarov, S.V.; Sukhov, V.N.; Churilov, I.G. (STC “Institute for Single Crystals”, 2011)
The paper presents the results of exploring the temperature range of formation and thermal stability of the AgCl and NaCl liquid phase in the islands condensed to Ni substrate in vacuum. It is established that the change of the mechanism of condensation from vapour-crystal to vapour-liquid at the deposition of the films of these chemical compounds is observed when the temperatures of the substrate is lower than their melting temperature. The values of supercooling at crystallization on the nickel substrate of island films of substances under study are determined, which make 95 K for AgCl and 369 K for NaCl, respectively. It is shown that the method of studying supercoolings which uses vacuum condensates is applicable to a broad range of substances. Приводятся результаты исследований температурного интервала образования и температурной устойчивости жидкой фазы в островковых вакуумных конденсатах хлоридов серебра и натрия на никелевых подложках. Установлено, что смена механизма конденсации от пар-кристалл к пар-жидкость при осаждении пленок этих химических соединений наблюдается при температурах подложки ниже температуры их плавления. Определены величины переохлаждений при кристаллизации островковых пленок исследуемых веществ на никелевой подложке, которые составили 95 и 369 К для AgCl и NaCl, соответственно. Показано, что метод изучения переохлаждений с использованием вакуумных конденсатов пригоден для широкого класса веществ. Наводяться результати досліджень температурного інтервалу утворення та температурної стійкості рідкої фази в острівцевих вакуумних конденсатах хлоридів срібла і натрію на нікелевих підкладках. Встановлено, що зміна механізму конденсації від пара-кристал до пара-рідина при осадженні плівок цих хімічних сполук спостерігається при температурах підкладки нижче температури їх плавлення. Визначено величини переохолоджень при кристалізації острівцевих плівок досліджуваних речовин на нікелевій підкладці, які склали 95 та 369 К для AgCl і NaCl, відповідно. Показано, що метод вивчення переохолоджень з використанням вакуумних конденсатів придатний для широкого класу речовин.
Keywords: Thin films; Wetting; Supercooling